Penetapan Harga dalam Jual Beli Perspektif Fikih Muamalah (Studi Komparasi Mazhab Maliki dan Mazhab Syafii) - Jamaluddin Jamaluddin; Sofyan Nur; Muhammad Taufan Djafri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This research was conducted with the aim of knowing the concept of buying and selling in Islamic muamalah, and to find out the pricing according to the Syafii and Maliki schools. The type of research used in this research is descriptive qualitative. Qualitative is a type of research that takes data sources from library books (library research). The author provides a response from the view of the Maliki school, that the concept adopted by the Maliki school is a concept that is in accordance with current market developments. The Maliki School also explains that the government's role in the economy is to oversee the market so that it operates normally without market intervention. However, nowadays there is little government intervention in the economy, such as intervention in the fuel (fuel) issue. Because the shape of the market today is more complex, operationally there are slight differences. As for the Syafii school of thought, it goes back to the concept of the market at the time of the Prophet Muhammad. which the government may not intervene in price fixing in buying and selling.